Uma estimativa do tipo L1 para potencial de Riesz - Hoshijima, Raphael Shoji (Universidade Federal de São Carlos, 2019)
In this work we will present a L1-type estimates for the Riesz potentials envolving the Riesz transform. This estimate is an improvement of result due to Stein and Weiss the result of Stein and Weiss that provides Riesz potentials is bounded in Hardy space. Such estimate was proved by Armin Schikorra, Daniel Spector and Jean Van Schaftingen in the paper “An L1-type estimate for Riesz potentials”, published in the Revista Matemática Iberoamericana in 2016.
An L1-type estimate for Riesz potentials
Keywords: Potencial de Riesz; Transformada de Riesz; Estimativa L1; Riesz Potentials; Riesz Transform; L1estimate; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE